Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1037/0022-3514.73.3.495
|View full text |Cite
|
Sign up to set email alerts
|

Is empathy-induced helping due to self–other merging?

Abstract: IWo experiments tested the idea that empathy-induced helping is due to self-other merging. To manipulate empathy, half of the participants in each experiment received instructions to remain objective while hearing about a young woman in need (low-empathy condition), and half received instructions to imagine her feelings (high-empathy condition). Tb check generality of the empathyhelping relationship, half in each empathy condition learned that the young woman was a student at their university (shared group mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
395
4
12

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(436 citation statements)
references
References 31 publications
25
395
4
12
Order By: Relevance
“…We show the conditions under which people take more from close others, which may appear to contradict the well-researched and intuitively plausible notion that interpersonal closeness should decrease taking because people care more about close versus distant others (Batson et al 1997;Cross, Bacon, and Morris 2000). Indeed, past research has shown increased closeness can lead people to treat others better, which seems to imply increased giving and decreased taking (Clark 1983;Rusbult et al 2004).…”
Section: When Closeness Decreases Versus Increases Takingcontrasting
confidence: 47%
See 2 more Smart Citations
“…We show the conditions under which people take more from close others, which may appear to contradict the well-researched and intuitively plausible notion that interpersonal closeness should decrease taking because people care more about close versus distant others (Batson et al 1997;Cross, Bacon, and Morris 2000). Indeed, past research has shown increased closeness can lead people to treat others better, which seems to imply increased giving and decreased taking (Clark 1983;Rusbult et al 2004).…”
Section: When Closeness Decreases Versus Increases Takingcontrasting
confidence: 47%
“…At the emotional level, closeness is shown as an increased liking of the relationship partner (Rubin 1970). At the cognitive level, closeness manifests as the overlapped mental representation of self and other (Aron et al 1991) that goes by various names in the literature, including self-other merging (Batson et al 1997), cognitive interdependence (Kelley and Thibaut 1978), and oneness (Cialdini et al 1997). Aron, Aron, and Smollan (1992) measured the self-other overlap via a set of Venn-like diagrams, each of which consists of two circles-one representing the self and one representing the other-that overlap to different degrees, from not at all to completely.…”
Section: Interpersonal Closeness: When You and I Become "We"mentioning
confidence: 99%
See 1 more Smart Citation
“…Compassion is evoked by witnessing or learning about others' physical or emotional pain (Batson et al, 1997;Condon & DeSteno, 2011;Eisenberg et al, 1989;Stellar, Cohen, Oveis, & Keltner, 2014;Stellar, Feinberg, & Keltner, 2014;Stellar, Manzo, Kraus, & Keltner, 2012;Van Kleef et al, 2008) or victimization (Cameron & Payne, 2011;Valdesolo & DeSteno, 2011a), and by viewing depictions of suffering others such as homeless or malnourished people (Oveis et al, 2009;Oveis, Horberg, & Keltner, 2010).…”
mentioning
confidence: 99%
“…In intergroup settings, empathy felt toward outgroup members generalizes into positive outgroup attitudes and helping intentions toward outgroup members (e.g., Batson et al, 1997;Galinsky & Moskowitz, 2000). Trust, on the other hand, is a positive psychological bias INTERMINORITY EXTENDED CONTACT 6 toward others (Yamagishi & Yamagishi, 1994).…”
Section: Outgroup Empathy and Outgroup Trustmentioning
confidence: 99%